Association between sleep duration and chronic lung diseases among Chinese middle-aged and older adults: A cross-sectional study - Caixia Yang; Li Xu (PLoS ONE, 2026)
Background Chronic lung diseases (CLDs) continue to be a major global public health concern. Previous studies have produced inconsistent findings regarding the relationship between sleep duration and CLDs. This study aimed to examine the association between sleep duration and CLDs in Chinese middle-aged and elderly adults. Methods This cross-sectional study used data from the 2011 survey of the China Health and Retirement Longitudinal Study (CHARLS). Self-reported sleep duration was collected using a structured questionnaire, and CLDs was defined by self-reported physician diagnosis. Multiple logistic regression models were employed to examine the association between sleep duration and CLDs. We used generalized additive model and smoothing fitted curves to examine whether nonlinear relationship existed. Results A total of 13,759 participants were included. Among participants, 5,773 (42.0%) slept less than 7 hours, 4,711 (34.2%) slept between 7–8 hours, and 3,275 (23.8%) slept more than 8 hours. After adjusting for all covariates, logistic regression showed a positive association between short sleep duration (< 7 hours) and CLDs (OR 1.29, 95% CI 1.10–1.52) compared to the normal group (7–8 hours). In addition, smoothing fitted curves indicated the existence of a non-linear association between sleep duration and CLDs. Conclusions Short sleep duration was associated with a higher likelihood of CLDs in Chinese middle-aged and elderly population. Further investigations are warranted to test this association.